Micronutrients accumulation in sunflower plants - Sfredo, Gedi Jorge; Sarruge, José Renato (Pesquisa Agropecuaria Brasileira, 2014)
In order to study the accumulation of the micronutrients by sunflower plants a field experiment was carried out at the "Centro Nacional de Pesquisa de Soja" in Londrina, PR, Brazil. Six fertilizer doses of NPK were used but in the only the dose 0-0-0 was examined, which caused greater production of dry matter and of achenes. Samples of plants were harvested from 14 days after emergence to the end of plant cicle. The highest rate of growth occurred at 42 day after emergence; the highest accumulation of Cu and Zn occurred in the achenes; the maximum accumulation of micronutrients for a production of 1,000 kg achenes were Fe = 933; Mn = 787; 13 = 285; Zn = 255 and Cu = 102 g; the exportation of the micronutrients correspondent to a production of 1,000 kg achenes were Fe = 69; Mn = 60; Zn = 59; Cu = 23 and 13 = 12 g.